2020
DOI: 10.1111/1365-2435.13641
|View full text |Cite
|
Sign up to set email alerts
|

Between predators and parasitoids: Complex interactions among shelter traits, predation and parasitism in a shelter‐building caterpillar community

Abstract: 1. Shelter-building is widespread in the animal world and such shelters often influence the success of their builders. Shelters built by caterpillars influence the likelihood of attacks by natural enemies, but how particular shelter traits influence caterpillar survival is not known. Furthermore, the differential effects of certain shelter traits on some natural enemies, such as predators, may lead to 'enemy-free space' for other natural enemies (parasitoids). The parasitoid enemy-free space hypothesis has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 73 publications
1
18
0
Order By: Relevance
“…Conversely, herbivores might seek refuge from predators under more stable and favorable climatic conditions (Tvardikova & Novotny, 2012), where predation pressure on larger herbivores is often high (Romero et al, 2018). It is, therefore, likely that herbivores use leaf shelters more as a refuge against natural enemies (Baer & Marquis, 2020) than for protection against aridity—this hypothesis might be further tested by adding a further treatment to the experiment proposed above, that is, leaf rolls made of transpiring versus non‐transpiring material, consisting of leaf rolls with apparatus preventing predator occupancy, thereby allowing us to tease apart the respective benefits of shelter use for herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, herbivores might seek refuge from predators under more stable and favorable climatic conditions (Tvardikova & Novotny, 2012), where predation pressure on larger herbivores is often high (Romero et al, 2018). It is, therefore, likely that herbivores use leaf shelters more as a refuge against natural enemies (Baer & Marquis, 2020) than for protection against aridity—this hypothesis might be further tested by adding a further treatment to the experiment proposed above, that is, leaf rolls made of transpiring versus non‐transpiring material, consisting of leaf rolls with apparatus preventing predator occupancy, thereby allowing us to tease apart the respective benefits of shelter use for herbivores.…”
Section: Discussionmentioning
confidence: 99%
“…As far back as the inception of the hypothesis parasitoids have been mentioned as potential higher trophic level species that are heavily influenced by enemy-free space (Jefferies and Lawton 1984). While little work on enemy-free space for parasitoids followed since that pivotal paper, almost all studies have found results that support the hypothesis and its predictions (Völkl 1992, Kaneko 2003, Murphy et al 2014, Baer and Marquis 2020. Ant attendance of an aphid species has been found to provide enemy-free space for both the aphid species and its primary parasitoids (Völkl 1992, Kaneko 2003.…”
Section: Enemy-free Space For Parasitoidsmentioning
confidence: 99%
“…It is noteworthy for the present study that this initial test did not distinguish these measures of parasitism and predation among caterpillar species living in the same site and year. Baer and Marquis (2020) tested the predictions of the enemy-free space hypothesis in a study of parasitoids that utilize shelter-building caterpillar hosts.…”
Section: Enemy-free Space For Parasitoidsmentioning
confidence: 99%
See 2 more Smart Citations